2012
DOI: 10.1161/strokeaha.111.636266
|View full text |Cite
|
Sign up to set email alerts
|

Subacute Ischemic Stroke Is Associated With Focal 11 C PiB Positron Emission Tomography Retention But Not With Global Neocortical Aβ Deposition

Abstract: Background and Purpose-Conflicting evidence exists as to whether focal cerebral ischemia contributes to cerebral amyloid deposition. We aimed to look at A␤ deposits, detected by N-methyl-2-(4Ј-methylaminophenyl)-6-hydroxybenzothiazole (PiB) positron emission tomography, in patients with recent ischemic stroke. Specifically, we hypothesized that patients with recent ischemic stroke have higher local and neocortical PiB positron emission tomography retention and that this may be associated with major vascular ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 40 publications
0
30
0
4
Order By: Relevance
“…59 Moreover, the possibility that the observed increase in local PiB retention being a result of leakage of free PiB because of the blood-brain barrier damage could not be excluded. 30 Overall, thus far, there is no solid evidence of a significant interaction between cerebral infarcts and global amyloid burden. …”
Section: Infarcts and Amyloid Plaquesmentioning
confidence: 99%
See 3 more Smart Citations
“…59 Moreover, the possibility that the observed increase in local PiB retention being a result of leakage of free PiB because of the blood-brain barrier damage could not be excluded. 30 Overall, thus far, there is no solid evidence of a significant interaction between cerebral infarcts and global amyloid burden. …”
Section: Infarcts and Amyloid Plaquesmentioning
confidence: 99%
“…59 Moreover, the possibility that the observed increase in local PiB retention being a result of leakage of free PiB because of the blood-brain barrier damage could not be excluded. 30 Overall, thus far, there is no solid evidence of a significant interaction between cerebral infarcts and global amyloid burden. Амилоидные бляшки представляют собой отложе-ния белка β-амилоида (Аβ) в веществе головного мозга и считаются одним из нейропатологических диагнос-тических признаков болезни Альцгеймера (БА) [1].…”
Section: Infarcts and Amyloid Plaquesunclassified
See 2 more Smart Citations
“…In a recent study, PiB-PET was performed a few days after stroke, and, in 20 out of 21 individuals, there was higher PiB retention in the ipsilateral peri-infarct brain region than in the contralateral side. 158 In one recent longitudinal study, baseline severity of white matter lesions correlated with increased PiB retention after a mean follow-up interval of 28 months. 78 The authors suggested that the association between WMH --a sign of CVD --and progression of amyloid load might be mediated by impaired amyloid clearance due to vascular damage.…”
Section: Unraveling the Relationship Between Ad And Cardiovascular Rimentioning
confidence: 95%